TACI Contributes to Plasmodium yoelii Host Resistance by Controlling T Follicular Helper Cell Response and Germinal Center Formation - Parra, Marcela; Yang, Jiyeon; Weitner, Megan; Derrick, Steven; Yang, Amy; Schmidt, Thomas; Singh, Balwan; Moreno, Alberto; Akkoyunlu, Mustafa (Frontiers in Immunology, 2018)
The delay in parasite-specific B cell development leaves people in malaria endemic areas vulnerable to repeated Plasmodium infections. Here, we investigated the role of transmembrane activator and calcium-modulator and cyclophilin ligand receptor (TACI), a molecule involved in the generation of antigen-specific antibody secreting cells, in host response to non-lethal Plasmodium yoelii infection. We found that TACI deficiency not only resulted in higher peak parasitemia levels in P. yoelii challenged mice, but also led to a delay in parasite clearance and anti-P. yoelii Merozoite Surface Protein 1(C-terminal 19-kDa fragment [rMSP-119]) protein and anti-rMSP-119 and anti-P. yoelii IgG antibody development. There was also a delay in the generation of splenic high affinity antibody secreting cells that recognize rMSP-119 protein as compared to wild-type mice. Interestingly, coinciding with the delay in parasite clearance there was a delay in the resolution of T follicular helper (Tfh) cell and germinal center (GC) B cell responses in TACI -/- mice. The persistence of Tfh and GC B cells is likely a result of enhanced interaction between Tfh and GC B cells because inducible costimulator ligand (ICOSL) expression was significantly higher on TACI -/- GC B cells than wild-type cells. Nevertheless, following the recovery from P. yoelii infection, TACI -/- and wild-type mice were both protected from a rechallenge infection. Establishment of protective B cell response was responsible for the resolution of parasitemia because B cells purified from recovered TACI -/- or wild-type mice were equally protective when introduced to naïve wild-type mice prior to P. yoelii challenge. Thus, despite the increased susceptibility of TACI -/- mice to P. yoelii infection and a delay in the development of protective antibody levels, TACI -/- mice are able to clear the infection and resist rechallenge infection.